Comparison of the Buschke Selective Reminding Test and the California Verbal Learning Test-Second Edition in a stroke population. Issue 6 (2nd November 2018) - Campbell, McKenzie E. M.; Leitner, Damian; Miller, Harry B.; Libben, Maya
ABSTRACT: There are many tests of learning and memory; however, not all yield analogous results and thus are not interchangeable. This study examined the relationship between the California Verbal Learning Test–Second Edition (CVLT-II) and the Buschke Selective Reminding Test (SRT) in a stroke population. Data from stroke inpatients ( N = 102) referred for rehabilitation were collected from medical records. Both tests were administered, as part of a larger neuropsychological assessment. Analyses were conducted on Z -scores from the List Total, Learning, and Long Delay Free Recall (LDFR) subscales of the two tests. SRT and CVLT-II scores were significantly correlated ( r = .34 to .52, all p values <.001). However, scores were significantly worse on the SRT compared to the CVLT-II ( d = −.90 to − 1.46, all p values <.001). Left hemisphere strokes performed worse than right hemisphere strokes on both tests; however, this trend was not significant. The SRT appeared to be more sensitive to impairment than the CVLT-II; thus, the two tests may not be interchangeable in a stroke population.